Power relations in Sudan after the fall of Bashir: From revolution to war - Gerrit Kurtz (Stiftung Wissenschaft und Politik (SWP), 2024)
War has raged in Sudan since April 2023 following fundamental changes in the political balance of power in recent years. The previously dominant security sector is deeply divided and the once weakly organised civil society has mobilised. Competition within the security sector made it possible to form a civil-military transitional government. Yet the continued rise to power of the Rapid Support Forces increased the risk of armed conflict, especially after the coup in 2021. Since Bashir's fall in 2019, the security forces have twice tried in vain to establish sole military rule. The civil-military transitional government also failed because the military still had considerable power resources at its disposal. Sudan's political elite contributed to this outcome by paying too little attention to the establishment of transitional institutions and too much attention to its own visibility. International actors who wanted to strengthen Sudan's transition process could have repelled the security forces more decisively instead of reflexively accepting them. Many international as well as Sudanese efforts suffered from the fact that they viewed the inclusion or exclusion of the security forces as a binary issue. A new non-inclusive, elitist deal with Sudan's violent entrepreneurs will not bring peace if there are no civilian forces at the table. Instead, Sudan's best chance lies in the social capital of its citizens' voluntary commitment to humanitarian aid, democracy and local reconciliation.
Keywords: 320; Sudan; security sector; civil-military transitional government; transition process; Sudanese Armed Forces (SAF); Rapid Support Forces (RSF); Omar al-Bashir; Prime Minister Hamdok; Hemedti